What Documents Do Not Do: Papering Persecution and Moments of Recognition in a Congolese Refugee Camp - Thomson, Marnie Jane (Anthropologica, 2018)
Congolese refugees living in Tanzania's Nyarugusu refugee camp curate and submit documents to the United Nations High Commissioner for Refugees (UNHCR) to bolster their cases for resettlement. UNHCR representatives often resist receiving these documents, and if received, they view them as supplementary to the case. The resettlement process requires that refugees prove that they fled their homeland because of individual persecution. However, an examination of the types of documents that refugees submit to the UNHCR, shows that they do not actually provide proof of persecution. Nonetheless, both refugees and UNHCR representatives use the documents to construct a convincing narrative of persecution that can successfully pass through the resettlement process.